PERLINDUNGAN HUKUM BAGI PIHAK DEBITOR DAN KREDITOR BARU PADA PROSES TAKE OVER ATAS ROYA HT-EL YANG DILAKUKAN OLEH KREDITOR LAMA - Wahyuni Y, Sri; Said, Nurfaidah; Marwah, Marwah (Universitas Ekasakti, 2023)
This study examines and analyzes the legal protection for parties, namely new debtors and creditors in the case of HT-el roya when paying off debt by third parties. This research is an empirical study, with a population of all Land Offices as mortgage service providers, BUMN Banks as creditors, and all Notaries/PPATs in South Sulawesi Province. The sample is determined by purposive sampling. Data collection techniques were conducted by interviews and analyzed by qualitative methods. The results of the study show that one form of legal protection that can be exercised for the debtor is to include a clause regarding mortgage rights in the credit agreement, including the time limit for filing royalties and the fees charged for the process. Thus, the debtor gets certainty over the cleaning of the mortgage guarantee. Whereas for new creditors the usual efforts are made when the party has not been able to register mortgage rights on collateral due to roya reasons, namely by making a Power of Attorney for Imposing Mortgage Rights (SKMHT). In addition, it can also be done by way of subrogation.